Flavonoid compounds as reversing agents of the P-glycoprotein-mediated multidrug resistance: An in vitro evaluation with focus on antiepileptic drugs - Ferreira, Ana (2018)
The pharmacoresistance to antiepileptic drugs (AEDs) remains a major unsolved therapeutic need. The overexpression of multidrug transporters, as the P-glycoprotein (P-gp), at the level of the blood-brain barrier of epileptic patients has been suggested as a key mechanism underlying the refractory epilepsy. Thus, efforts have been made to search for therapeutically useful P-gp inhibitors. Herein, the strategy of flavonoid/AED combined therapy was exploited as a possible approach to overcome the P-gp-mediated pharmacoresistance. For this purpose, several in vitro studies were performed using Madin-Darby canine kidney II (MDCK II) cells and those transfected with the human multidrug resistance-1 (MDR1) gene, overexpressing the P-gp (MDCK-MDR1). Overall, the results showed that baicalein, (−)-epigallocatechin gallate, kaempferol, quercetin and silymarin, at 200 μM, produced a marked increase on the intracellular accumulation of rhodamine 123 in MDCK-MDR1 cells, potentially through inhibiting the P-gp activity. In addition, with the exception of lamotrigine, all other AEDs tested (phenytoin, carbamazepine and oxcarbazepine) and their active metabolites (carbamazepine-10,11-epoxide and licarbazepine) demonstrated to be P-gp substrates. Furthermore, the most promising flavonoids as Pgp inhibitors promoted a significant increase on the intracellular accumulation of the AEDs (excluding lamotrigine) and their active metabolites in MDCK-MDR1 cells, evidencing to be important drug candidates to reverse the AED-resistance. Thus, the co-administration of AEDs with baicalein, (−)-epigallocatechin gallate, kaempferol, quercetin and silymarin should continue to be explored as adjuvant therapy for refractory epilepsy.